A unique record of Cercis from the late early Miocene of interior Asia and its significance for paleoenvironments and paleophytogeography. Issue 6 (24th July 2020) - Li, Xiang‐Chuan; Manchester, Steven R.; Wang, Qin; Xiao, Liang; Qi, Tian‐Long; Yao, Yun‐Zhi; Ren, Dong; Yang, Qiang
Abstract: The climatic impacts of the Tibetan Plateau since the Neogene and the phytogeographic pattern changes of formerly widely‐distributed forest communities on the plateau remain poorly constrained. Today, Cercis L. (Fabaceae) is a well‐known arborescent genus typically distributed in subtropical to warm temperate zones of the Northern Hemisphere, and Paleogene fossil occurrences from Eurasia and North America show a long history of the genus in mid‐low latitudes of the Northern Hemisphere. Here, we describe a fossil species, Cercis zekuensis sp. nov. based on well‐preserved fruits from the early Miocene of the northeastern Tibetan Plateau. Detailed morphological comparison (e.g., ventral margin with a veinless wing) of extant and fossil members of Cercis and other genera confirmed validity of the present taxonomic identity. Based on the comparison with extant relatives and their climate preferences, this unexpected occurrence of thermophilic Cercis in northeastern Tibetan Plateau indicates this area had higher temperature and precipitation in the Miocene than today. Integrated with inferred (paleo‐)temperature lapse rates, this indicates a low paleoelevation of less than 2.4 km. In contrast with the present‐day alpine climate here (~3.7 km), such a low elevation facilitated a more favorable habitat with comparatively high biodiversity and warm temperate forests at that time, as were evidenced by co‐occurring megafossils. Moreover, the present existence of Cercis implies the genus was widespread in interior Asia during the early Neogene and shows its modern disjunction or diversification between eastern and central Asia was possibly shaped by the late Cenozoic regional tectonic uplift and consequential environmental deterioration.